Recent progress in Fenton/Fenton-like reactions for the removal of antibiotics in aqueous environments - Yu Jiang (Ecotoxicology and Environmental Safety, 2022)
The frequent use of antibiotics allows them to enter aqueous environments via wastewater, and many types of antibiotics accumulate in the environment due to difficult degradation, causing a threat to environmental health. It is crucial to adopt effective technical means to remove antibiotics in aqueous environments. The Fenton reaction, as an effective organic pollution treatment technology, is particularly suitable for the treatment of antibiotics, and at present, it is one of the most promising advanced oxidation technologies. Specifically, rapid Fenton oxidation, which features high removal efficiency, thorough reactions, negligible secondary pollution, etc., has led to many studies on using the Fenton reaction to degrade antibiotics. This paper summarizes recent progress on the removal of antibiotics in aqueous environments by Fenton and Fenton-like reactions. First, the applications of various Fenton and Fenton-like oxidation technologies to the removal of antibiotics are summarized; then, the advantages and disadvantages of these technologies are further summarized. Compared with Fenton oxidation, Fenton-like oxidations exhibit milder reaction conditions, wider application ranges, great reduction in economic costs, and great improved cycle times, in addition to simple and easy recycling of the catalyst. Finally, based on the above analysis, we discuss the potential for the removal of antibiotics under different application scenarios. This review will enable the selection of a suitable Fenton system to treat antibiotics according to practical conditions and will also aid the development of more advanced Fenton technologies for removing antibiotics and other organic pollutants.